FISCAL PROBLEMS IMBALANCES AND POSSIBLE RISKS WHICH ARISE FROM THEM IN POST CRISIS PERIOD - Đurić, Dejan; Živkov, Dejan; Kolar, Suzana (Economics of Agriculture, 2011)
Appearance of the global crisis in 2008. forced financial markets to colaps. Main consequence of the world recession was sudden fall of agregate demand and unemployment rise. Government has appeared in that conditions as the only subject who could bring back economy on precrisis level with help of axcessive consumption. We are now witnessing that intervention measures have been successful, however new threat are looming in form of high budget deficits and huge public debts. Basic methods applied in this paper are analytical and empirical which could help to understand and overview observed problem.